Use of deltamethrin 'pour on' insecticide for the control of cattle trypanosomiasis in the prescence of high tsetse invasion - Rowlands, G.J.; Leak, S.G.A.; Mulatu, W.; Nagda, S.M.; Wilson, A.; D'Ieteren, G.D.M. (Wiley, 2001)
A deltamethrin `pour-on' insecticide was applied monthly to over 2000 cattle exposed to a high challenge of drug-resistant trypanosomes and high tsetse re-invasion pressure in the Ghibe valley, south-west Ethiopia. Blood samples were taken monthly from an average of 760 cattle for determination of PCV and presence of trypanosomes. The area of the valley is approximately 350 km2 and the cattle grazed in roughly four locations covering about a quarter to half of the area. Two years before the trial commenced, Glossina morsitans submorsitans. Newstead (Diptera: Glossinidae) began to invade the valley. Despite the use of the pour-on the mean apparent density of G. m. submorsitans continued to rise. and, during the 4 years of tsetse control, was more than three-fold higher than that recorded during the previous 18 months. Over the same period there was little change in the apparent density of Glossina pallidipes Austen (Diptera: Glossinidae). By contrast. the mean monthly prevalence of trypanosome infections in cattle over 36 months of age decreased from 38.3 to 29.0%, the incidence of new infections decreased from 26.6 to 16.0%: (a reduction of 40%), and packed cell volume in cattle increased from 21.7 to 24.1%. Evidence of a change in apparent parasite transmission rate was demonstrated by regression of infection incidence in cattle on the logarithm of apparent density of G. m. submorsitans. Before the trial started the regression coefficient was 45.8 ± 6.3 and this reduced to 9.2 ± 2.5% incidence per loge (flies/ trap/day) during the period of tsetse control. It was concluded that this indicated reductions in tsetse numbers in the immediate vicinities of cattle in a way that was not reflected in overall tsetse catches. Nevertheless, the comparatively high levels of trypanosome prevalence that persisted in the cattle demonstrates that, where invasion prevalence is high, treatment of small pockets of cattle will not eradicate tsetse. To achieve more significant reduction in trypanosome prevalence in cattle integrated methods of control utilizing target barriers in the major routes of invasion will be needed.